Fiqh Entertainment dalam Komunikasi Kesehatan Kasus Keluarga Berencana (KB) - Sayid Qutub (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2015)
Keluarga Berencana (KB) is a government program that aims to achieve an increase in a mother and family welfare. KB is the setting for the welfare of pregnancy spacing. Thus realizing a healthy family. KB is allowed to keep the mother and child health remains stable. However it is prohibited if KB is intended to break the descent, KB should not be the deciding goal descendants permanently as vasectomy and tubectomy. With effective health communication implementation of KB, it is expected to run well and smoothly and the government can socialize it well.